A comparison of blockchain application and security issues from Bitcoin to Cybersecurity - Fahmi, Novandio; Hastasakti, Diki Edwin; Zaspiagi, Diaz; Saputra, Rino Kurniawan; Wijayanti, Septi (Blockchain Frontier Technology, 2023)
Blockchain has quickly emerged as one of the trendiest Internet technologies in recent years due to the fast pace of technological advancement. With its integrated cryptography and consensus process, blockchain has redefined trust as a decentralized and distributed data management solution, ensuring security, privacy, and data integrity without the involvement of a third party. However, there are still certain technological difficulties and restrictions with blockchain. This essay has studied the present blockchain applications in cybersecurity in a methodical manner. The paper evaluates the benefits that blockchain has brought to cybersecurity and provides a summary of recent studies and blockchain applications in cybersecurity-related fields in order to address the security challenges. The paper presents four key security challenges of blockchain through in-depth research and overview of the existing work, and then conducts a more detailed investigation of each issue. The research also propos